Governance Collaboration for Enhancing Regional Original Revenue (A Bibliometric Approach to Research Development) - Parlina, Rina; Simangunsong, Fernandes; ., Rizari; Haposan, Tumpak (Journal of Posthumanism, 2025)
This research, titled "Collaborative Governance in Increasing Original Regional Income (A Bibliometric Approach to Research Development)," aims to explore research trends on collaborative governance through a bibliometric study. The study identifies scientific publications used in various academic studies and aims to position this research within the field of Government Science, while examining the global development of the "collaborative governance" research theme. The initial step involved retrieving article documents from Scopus, followed by processing bibliometric data using the VOSviewer application. The search resulted in 48 articles, which were further analyzed to identify growth and potential research opportunities. The study revealed that research on collaborative governance, particularly in enhancing local revenue in Indonesia, is still limited, highlighting the need for further studies in this area. The majority of studies are concentrated in the realm of Government Science, reflecting the importance of collaborative governance as a tool for implementing public policies. The research also identified trends in collaborative governance research globally, with the United States, the United Kingdom, and China leading in terms of publication volume. However, Indonesia has yet to rank among the top ten countries in this field, presenting an opportunity for researchers to contribute to policy network studies. Overall, this bibliometric analysis emphasizes the significance of expanding collaborative governance research to enhance the effectiveness of public decision-making processes and improve governance practices across various levels.